Giving Students the Competitive Edge. (Communications of the ACM, 2012)
The author describes the Association for Computing Machinery (ACM) International Collegiate Programming Contest (ICPC) held at the University of Warsaw in Warsaw, Poland from May 14 - 18, 2012. Topics include computing and big data research from sponsor International Business Machines Corp. (IBM), the World Finals for computer programming, and an invitation from Russian president Vladimir Putin for the competition winners to attend the Russian Federation Academy of Science annual meeting.